2016
DOI: 10.1038/ncomms13814
|View full text |Cite
|
Sign up to set email alerts
|

Origin of stabilization and destabilization in solid-state redox reaction of oxide ions for lithium-ion batteries

Abstract: Further increase in energy density of lithium batteries is needed for zero emission vehicles. However, energy density is restricted by unavoidable theoretical limits for positive electrodes used in commercial applications. One possibility towards energy densities exceeding these limits is to utilize anion (oxide ion) redox, instead of classical transition metal redox. Nevertheless, origin of activation of the oxide ion and its stabilization mechanism are not fully understood. Here we demonstrate that the suppr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

47
488
2
2

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 391 publications
(539 citation statements)
references
References 43 publications
47
488
2
2
Order By: Relevance
“…Since superoxide species is chemically unstable, which results in the oxidation and decomposition on further charge to 4.8 V. Indeed, after charge to 4.8 V, intensity of superoxide-like species is significantly weakened, indicating decomposition of superoxide-like species on charge to 4.8 V. Such decomposition reaction of superoxide species leads to oxygen loss, which triggers the structural reconstruction process, and thus Fe and Mo are reduced on discharge. Note that the formation of superoxide species was not evidenced for Li-Nb-Mn system, 8,20 and therefore it is concluded that the suppression of the formation of superoxide-like species is important to improve the reversibility of solid-state redox reaction of oxide ions.…”
Section: ¹1mentioning
confidence: 99%
“…Since superoxide species is chemically unstable, which results in the oxidation and decomposition on further charge to 4.8 V. Indeed, after charge to 4.8 V, intensity of superoxide-like species is significantly weakened, indicating decomposition of superoxide-like species on charge to 4.8 V. Such decomposition reaction of superoxide species leads to oxygen loss, which triggers the structural reconstruction process, and thus Fe and Mo are reduced on discharge. Note that the formation of superoxide species was not evidenced for Li-Nb-Mn system, 8,20 and therefore it is concluded that the suppression of the formation of superoxide-like species is important to improve the reversibility of solid-state redox reaction of oxide ions.…”
Section: ¹1mentioning
confidence: 99%
“…When removing electron from pure O p states in the bulk, unstable oxyl species would be formed prior to stabilization by charge reorganization. While examples have now been given for the structurally more flexible layered compounds used as Li-ion battery positive electrodes [16,18,20], only rare examples describing the reorganization of lattice oxygen reorganization in the perovskite structure can be found. Indeed, due to the rigidity of the corner-shared octahedral arrangement and the relatively large O-O bond distance, this reorganization is foreseen to be almost impossible for cubic perovskites.…”
Section: Reactivity Of the Oxygen Species Formed Upon Oxidationmentioning
confidence: 99%
“…Identifying the difference between these two types of oxidized species formed under oxidation is also of prime importance for storing extra capacity in Li-ion battery cathode materials, since only the electron removal from lone pair orbitals offers the opportunity to exchange an extra electron upon charging in addition to the one classically exchange from the M-O* bond. Hence, several papers can be found in the literature regarding this phenomenon, with a common agreement in describing the anionic (or oxygen) redox reaction as involving oxygen lone pairs [16][17][18][19][20][21][22][23]. Definitively, it now appears that the chemistry of O-O bond formation, which is the cornerstone of the OER reaction for instance, involves specific electronic levels that we aim to describe in this manuscript.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…[1][2][3][4][5] Therefore, understanding the origin of the functionalities and the governing factors are important knowledge for further development of the energy conversion and storage technologies. The author and coworkers have been studying on understanding the origin of electrochemical properties of layered perovskite type La 2 NiO 4 -based oxides as a model system.…”
Section: Introductionmentioning
confidence: 99%